JUAN MÉNDEZ NIETO, GRANDSON, THE FIRST MEDICAL EDUCATORDE COLOMBIA (2012)
This article deals with Juan Méndez Nieto Portuguese doctor who practiced in Cartagena de Indias, from 1569 until his death in 1616, leaving the “Medical Discourses” an autobiographical text focusing on his medical practice, through which studied medicine at the time and social environment. No doubt the excellence Méndez Nieto brought us his medical knowledge up to time, mainly botanical pharmacopoeia. He was a true secular and medical educator who built a landmark ethics of the profession. In addition, precursor of clinical medicine, not only for their semiological experience, but was able to think in terms of pathophysiology and even to locate the disease process, which is quite significant, given his poor knowledge of anatomy and not advanced medical believings during the second half of the sixteenth century. He was a doctor with solid remarkable moral and ethical principles, which showed investigative concerns, concern for both, public health and the quality of care. All this, provided in his book “Medical Discourses”, a book that indicates us in its own style and structure, a great preparation and culture, a réflex of his author and its certain content, consistent in a true light for the knowledge of the time, which is reported appropriately the huge medical training of Doctor Méndez Nieto. Therefore, by analyzing their reports, highlight his book as the first medical textbook written in this city of Cartagena de Indias, Colombia in the Caribbean and throughout the country. We propose to Juan Méndez Nieto as the first medical educator of this new kingdom, Cartagena and Colombia. He was truly a cultural mediator who brought knowledge and seized the locals.